The experience of the interior: outlines of an alternative anthropology. (2nd January 2016) - Pint, Kris
Abstract: Cultural artifacts only acquire meaning in a subjective context. This is particularly the case for the domestic interior, which since modernity has a strong link with the subjects inhabiting them. Inspired by the later work of Michel Foucault, we want to present an approach to interiors that takes into account this subjectivity, not only of the inhabitant, but also of the researcher. Using the work of anthropologist Tim Ingold, we will argue that our bodily and existential engagement with an interior environment can be considered as a valid form of scholarship. Finally, we will apply this alternative anthropology in a short analysis of a painting by Pierre Bonnard.